Hypomethylation of STAT1 and HLA-DRB1 is associated with type-I interferon-dependent HLA-DRB1 expression in lupus CD8+ T cells. Issue 4 (23rd January 2019) - Miller, Shaylynn; Tsou, Pei-Suen; Coit, Patrick; Gensterblum-Miller, Elizabeth; Renauer, Paul; Rohraff, Dallas M; Kilian, Nathan C; Schonfeld, Mark; Sawalha, Amr H
Abstract : Objective: We examined genome-wide DNA methylation changes in CD8+ T cells from patients with lupus and controls and investigated the functional relevance of some of these changes in lupus. Methods: Genome-wide DNA methylation of lupus and age, sex and ethnicity-matched control CD8+ T cells was measured using the Infinium MethylationEPIC arrays. Measurement of relevant cell subsets was performed via flow cytometry. Gene expression was quantified by qPCR. Inhibiting STAT1 and CIITA was performed using fludarabine and CIITA siRNA, respectively. Results: Lupus CD8+ T cells had 188 hypomethylated CpG sites compared with healthy matched controls. Among the most hypomethylated were sites associated with HLA-DRB1 . Genes involved in the type-I interferon response, including STAT1, were also found to be hypomethylated. IFNα upregulated HLA-DRB1 expression on lupus but not control CD8+ T cells. Lupus and control CD8+ T cells significantly increased STAT1 mRNA levels after treatment with IFNα. The expression of CIITA, a key interferon/STAT1 dependent MHC-class II regulator, is induced by IFNα in lupus CD8+ T cells, but not healthy controls. CIITA knockdown and STAT1 inhibition experiments revealed that HLA-DRB1 expression in lupus CD8+ T cells is dependent on CIITA and STAT1 signalling. Coincubation of naïve CD4+ T cells with IFNα-treated CD8+ T cells led to CD4+ T cell activation, determined by increased expression of CD69 and cytokine production, in patients with lupus but not in healthy controls. This can be blocked by neutralising antibodies targeting HLA-DR. Conclusions: Lupus CD8+ T cells are epigenetically primed to respond to type-I interferon. We describe an HLA-DRB1+ CD8+ T cell subset that can be induced by IFNα in patients with lupus. A possible pathogenic role for CD8+ T cells in lupus that is dependent on a high type-I interferon environment and epigenetic priming warrants further characterisation.